Pendidikan Multikulturalisme dan Hak Asasi Manusia di Indonesia - Uun Yusufa (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: In a heterogeneus society, as in Indonesia, multicultural conflict contributed significantly to the crisis of culture and human right violations. Cultural interaction that is not harmonius or coercion between the cultural phenomenon of one over another has threatened the ideal of culture itself. Therefore, the required planting patterns in a more businesslike culture and heterogeneous to answer the crisis of culture. Awareness of multiculturalism and respect for human rights need to be inculcated in every student the education in our country. This paper attempts to describe how important and growing signicance of education in the world of multicultural education to be able to issues of conflict and human right violations are constantly palgued this nation. Keywords: Multiculturalism, Conflict, SARA, Human Right